GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 185896122 species occurrences available in GBIF matching the query: BasisOfRecord: Specimen or Fossil or Unknown evidence. The dataset includes 185896122 records from 12504 constituent datasets: 2 records from First report on Paratischeria from Asia (Lepidoptera: Tischeriidae). 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 3 records from Two new Brazilian species of Neapion Alonso-Zarazaga, 1990 subgenus Neotropion Alonso-Zarazaga, 1990 with a key to South American species (Brentidae: Apioninae). 96 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 48 records from A new species of Psilorhynchus (Teleostei: Psilorhynchidae) from the Ataran River Basin, Myanmar, with comments on the generic name Psilorhynchoides.. 13736 records from MfN - Mallophaga Collection. 11961 records from MEXU/Leguminosae. 2 records from Synchrotron micro-CT scanning leads to the discovery of a new genus of morphologically conserved echinoid (Echinodermata: Cassiduloida). 2 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 5262 records from Spider Mites Collection of Jean Gutierrez. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 609 records from Collection botanique Mulon L. (BOUM). 439 records from Implementación de la bioindicación en el Río Magdalena. 1 records from Redescription of the monotypic genus Cubacanthozomus (Schizomida: Hubbardiidae) and conservation status of its type-species. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 79254 records from CM Vertebrate Paleontology Collection. 446 records from Estudio ecológico-florístico de los enclaves de vegetación xerofítica inmersos en una selva baja caducifolia en el Istmo de Tehuantepec, Oaxaca. 1333 records from Sistematización de la colección de peces del centro de México. 407 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 62125 records from UCLA Donald R. Dickey Bird and Mammal Collection. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 3 records from Results of palynological analysis of Hole 302-M0004C. 135 records from Globigerinita spp. in sediment core MSM05/5_712-2. 26 records from Further revision of the genus Bythotrephes Leydig (Crustacea: Cladocera: Onychopoda): redescription of B. brevimanus Lilljeborg, reevaluation of B. cederströmii Schödler, and description of a new species of the genus. 2 records from Contribution to the knowledge of Himalayan and North Indian species of Scaphidium (Coleoptera, Staphylinidae). 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 61 records from The Onthophagus fuscus (Coleoptera: Scarabaeidae) species complex: an update and the description of a new species. 8984 records from Plant specimens of Obihiro Centennial City Museum. 794914 records from Western Australian Museum provider for OZCAM. 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 3 records from Two new Mesenchytraeus species (Annelida: Clitellata: Enchytraeidae) from Changbai Mountain, China. 1 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 3 records from A new species of highland vampire crab (Crustacea: Brachyura: Sesarmidae: Geosesarma) from Serian, Sarawak. 749 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 591 records from Alan Wormington Collection. 93 records from Benthic Foraminifera from the Capricorn Group, Great Barrier Reef, Australia. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 510 records from University of Saskatchewan. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 5 records from Revalidation of a moray eel, Gymnothorax mucifer Snyder, 1904 (Teleostei: Anguilliformes: Muraenidae), with a revised distribution. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1513 records from M. Gollop Collection. 37 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 7162 records from SMDB - Santa Maria Departamento de Biologia. 53203 records from Naturalis Biodiversity Center (NL) - Diptera. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 6 records from Review of the enigmatic genus Boalda with transfer of pulcherrima Köhler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 2 records from Schulhof Gymnasium Hürth Bonnstrasse. 13981 records from Flora of the Korean Peninsula. 235 records from Visual Plants (144.41.33.158) - Plants from Costa Rica; Helmut Dalitz. 1 records from Berlese's Primitive Oribatid Mites. 3 records from Notioperilitus gen. nov., a new braconid genus (Hymenoptera: Braconidae: Euphorinae) from Australia, parasitoid of adult Morabinae (Orthoptera: Eumastacidae), with remarks on the generic placement of two Afrotropical euphorine species. 157 records from Pheidole (Hymenoptera, Formicidae) of Middle American Wet Forest. 3 records from Two new species and the molecular phylogeny of eight species of Macrostomum (Platyhelminthes: Macrostomorpha) from southern China. 23 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 203 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 1562 records from Plathelminthes - SMF. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 13483 records from Insect specimens of Rikuzen-Takata City Museum. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 4 records from Re-visiting the Aphidius urticae s. str. group: re-description of Aphidius rubi Starý and A. silvaticus Starý (Hymenoptera: Braconidae: Aphidiinae). 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 356 records from Amphibia Collection of Museum and Institute of Zoology PAS. 18 records from A new species of Cintaroa from India and new records of Craspedophorus from Pakistan and the Philippines (Coleoptera: Carabidae: Panagaeini). 21794 records from Bryophyte specimens database of Mr. Tsutomu Kodama collection. 18940 records from Cowan Tetrapod Collection - Mammals. 2 records from A new tropical montane firefly genus and species, active during winter and endemic to the southeastern Atlantic Rainforest (Coleoptera: Lampyridae). 1818 records from Actualización de la información sobre los maíces criollos de Oaxaca. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 62 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 892 records from Pollen profile ADR309. 2 records from The fungus-growing ant genus Apterostigma in Dominican amber.. 34 records from The lestevoides species group of the genus Geodromicus Redtenbacher, 1857 (Insecta: Coleoptera: Staphylinidae: Omaliinae). 146 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 2 records from Zorotypus weiweii (Zoraptera: Zorotypidae), a new species of angel insects, from Sabah, East Malaysia. 16 records from Insect Collections of Okomu National Park- Nigeria. 235 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 19 records from Heinersdorfer Sumpfwiese. 291402 records from ARABEL - Arachnologia Belgica. 532 records from (Table 6) Distribution of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 9 records from A new troglobitic Tychobythinus from Sicily (Coleoptera, Staphylinidae, Pselaphinae). 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 348 records from Antarctic pycnogonids. 17672 records from LSUMZ (LSU MNS) Fishes Collection. 62776 records from MLZ Bird Collection (Arctos). 26 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 39 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 1 records from Naturschutzgebiet Müchelholz (Mücheln). 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 3 records from Wiese am Waldrand (Gurtweil). 186 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 4 records from Coeliccia lecongcoi sp. nov., a new damselfly from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae). 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 11 records from A new species of Trachylepis (Squamata: Scincidae) from Central Africa and a key to the Trachylepis of West and Central Africa. 1997 records from Lichen collection. 351 records from UWYMV Herpetology Collection (Arctos). 92061 records from Herbarium (ICEL). 102954 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from Zetes ephippiatus. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 13 records from New species, redescriptions and a new combination of Acanthocyrtus Handschin, 1925 and Amazhomidia Cipola & Bellini, 2016 (Collembola, Entomobryidae, Entomobryinae). 15827 records from Leiner-Herbar Konstanz. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 4 records from A new species of the ant genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae) from the Caribbean region. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 2007 records from Plant specimens of Bihoro Museum. 105 records from bmhs_moth_collection. 4090 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 4 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 272 records from Inventario de corales pétreos, asteroideos, equinoideos y peces óseos de arrecifes de la costa de Jalisco, Colima y Michoacán. 106 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 23 records from New and interesting species of the genus Bryaxis Kugelann, 1794 (Coleoptera, Staphylinidae, Pselaphinae) from Croatia. 944 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 237 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 395 records from Reptilia ZMK. 61 records from Relative abundance of coccosphere-units of sediment core GIK23071-2. 408 records from Birds Specimens of Akita Prefectural Museum. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 2745 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 407 records from Megafaunal data from the 2009 BIOFUN trans-Mediterranean deep-sea cruise. 46865 records from Sistematización del Herbario Nacional Forestal Biól Luciano Vela Gálvez. 26841 records from MSUM Ichthyology and Herpetology Collections. 5 records from Didogobius janetarum sp. nov., a new cryptobenthic goby species from the Cape Verde Islands (Teleostei: Gobiidae). 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 9 records from On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae). 371 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 8 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 1 records from A new species of Bathynomus Milne Edwards, 1879 (Isopoda: Cirolanidae) from The Bahamas, Western Atlantic. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 282 records from (Table 2) Distribution of some benthic foraminifera in ODP Hole 108-658A. 7 records from A new crayfish of the genus Cambarus Erichson, 1846 (Decapoda: Cambaridae) from an under-sampled habitat type in central Ten- nessee, USA. 1 records from Myolaimus ibericus sp. n. (Nematoda, Rhabditida, Myolaimidae) from southern Iberian Peninsula, with a key to species of the genus. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 7 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 3326 records from Plant specimens of Nasunogahara Museum. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 184807 records from Tiroler Landesmuseum Ferdinandeum. 89 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 9400 records from Colección de Mamíferos del Instituto Alexander von Humboldt. 2 records from New species of the Genus Haliclona (Haplosclerida: Chalinidae) from Korea. 854 records from Análisis de Integridad Biológica en la Reserva Forestal Protectora Regional Bitaco. Convenio CVC- Univalle 108 de 2017. 6 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 450 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 6729 records from Epibenthos and demersal fish monitoring at long-term monitoring stations in the Belgian part of the North Sea. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 1192 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 78 records from Mammals (GNHM-MM). 3 records from First description of the male of the easternmost Harpactea species, H. parthica (Araneae: Dysderidae). 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 30952 records from SANT-Algae. 672 records from Colección de Entomología - Curculionidae. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 843 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 9 records from Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini). 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 1262 records from (Appendix B) Abundance of dinoflagellates in sediment core MD01-2378. 29 records from Systematics, ecology and distribution of the mygalomorph spider genus Cteniza Latreille, 1829 (Araneae, Mygalomorphae, Ctenizidae). 2748478 records from International Barcode of Life project (iBOL). 2 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 4 records from Lectotype designation and distribution updates on the freshwater shrimp species Atyaephyra stankoi Karaman 1972. 3 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 19739 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 205 records from Japan Collection of Microorganisms(Basidio). 6237 records from Plecoptera. 22 records from MtDNA differentiation and taxonomy of Central Asian racerunners of Eremias multiocellata - E. przewalskii species complex (Squamata, Lacertidae). 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 5 records from Amphibia, Bokermannohyla nanuzae, Scinax curicica, Leptodactylus camaquara, Physalaemus evangelistai, and Proceratophrys cururu: Distribution extensions. 3 records from A new species of and a new transfer from the millipede genus Polydrepanum Carl, 1932 (Polydesmida, Paradoxosomatidae, Polydrepanini). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 43 records from Abundance of coccosphere-units of sediment core GIK23424-3. 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 1 records from Flora. 6 records from Free-living marine nematodes of Desmodorella and Zalonema (Nematoda: Desmodoridae) with description of two new species from the deep sea of the North Western Pacific. 58 records from Undercover speciation of wentletraps (Caenogastropoda: Epitoniidae) in the Southwestern Atlantic. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 280 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 14 records from Re-description of Coeliccia erici Laidlaw, and the description of Coeliccia sameerae sp. nov. from Peninsular Malaysia (Odonata: Zygoptera: Platycnemididae). 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 8 records from Reconsideration of the apterous carventine genus Crassocoris and description of Paracrassocoris gen. nov. from China (Hemiptera: Heteroptera: Aradidae). 34 records from NZCS Brownsberg Nature Park Monitoring. 143 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 3652 records from La flora útil de dos comunidades indígenas del Valle de Tehuacán-Cuicatlán: Coxcatlán y Zapotitlán de las Salinas, Puebla. 14 records from Collection Amphibia fossil SMF. 57845 records from Collection Mollusca SMF. 10 records from Two new records of the coral symbiont crab genus Quadrella Dana, 1851, from Taiwan, with notes on the taxonomy of Q. boopsis Alcock, 1898 (Crustacea: Brachyura: Trapeziidae). 12681 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleobotany National Collection (BAPb). 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 101 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 25 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 24 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 4 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 1289 records from Records of the Victorian Conservation Seedbank. 54 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 119366 records from The digitization of plant specimens of NTU. 208 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 4 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 851 records from (Table 3) Distribution of calcareous nannofossils at DSDP Site 82-563 in the North Atlantic. 1952 records from ISM Ichthyology Collection. 2 records from Aphaenogaster gamagumayaa sp. nov.: the first troglobiotic ant from Japan (Hymenoptera: Formicidae: Myrmicinae). 798 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 8259 records from Insect specimens of Okinawa Prefectural Museum & Art Museum. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 142891 records from The Himalayan Uplands Plant database (HUP Version 1). 38 records from (Supplement Table 5) Percentage cover abundance of plants recorded at the Primary Site on Disko Island. 8 records from Three new minute leaf litter beetles discovered by citizen scientists in Maliau Basin, Malaysian Borneo (Coleoptera: Leiodidae, Chrysomelidae). 1 records from Artenvielfalt auf dem Schulgelände. 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 1897 records from Royal BC Museum - Herpetology Collection. 5 records from Two new and one newly recorded species of Polypedilum Kieffer 1912 with DNA barcodes from Oriental China (Chironomidae: Diptera). 31015 records from National Museum of Natural Science. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 5426 records from Collection Francaise de Bacteries Phytopathogenes. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 7918 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 17 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1614 records from New Brunswick Museum Collection. 322 records from Collections ichtyologiques et herpétologiques (BOUM). 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 29 records from New dark species of the bee genus Colletes (Hymenoptera, Colletidae) from Mexico and Guatemala. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 65903 records from Norwegian Lepidoptera working group. 20 records from Taxonomic revision of Brazilian genus Tyrannoseira Bellini & Zeppelini, 2011 (Collembola, Entomobryidae, Seirinae). 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 10 records from A mountain of millipedes VI. New records, new species, a new genus and a general discussion of Odontopygidae from the Udzungwa Mts, Tanzania (Diplopoda, Spirostreptida, Odontopygidae). 38876 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 6202 records from Lichens of North-Eastern Poland. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 33 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 6 records from Exogoninae (Annelida: Syllidae) from Chilean Patagonia. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 1310925 records from Paleobiology Database. 3509 records from Entocytheridae (Ostracoda) World Database. 74 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 25 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 119 records from Pycnogonida collection from the Museu Nacional de História Natural e da Ciência da Universidade de Lisboa, Portugal. 1014 records from Pollen profile ADR353. 270 records from bmhs_weatherheadshell_collection. 1 records from Sächsische Schweiz (Pfaffenstein). 234 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 108 records from Studies in Hawaiian Diptera I: New Distributional Records for Endemic Asteia (Asteiidae). 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 285727 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 11 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 220 records from Living Cirripedia. 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 32 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 26 records from Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific). 2227 records from IRAD Cameroon insect collection. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 4310 records from MfN - Fossil vertebrates V. 13 records from On a collection of deep-water shrimp (Crustacea, Decapoda) from the Dutch Caribbean, with the description of a new species of Pseudocoutierea. 30 records from Averages and ranges of paleoenvironmental proxy records of ODP Hole 108-658C (Table 1). 463 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 209 records from Nannofossil abundance of Hole 94-610B. 1 records from Synchiropus sycorax, a new species of dragonet from the Philippines (Teleostei: Callionymidae). 9 records from Redescription of Isotoma grana Lee, Kim & Kim, 1993 and description of a new species of Isotoma Bourlet, 1839 (Collembola: Isotomidae) from Korea. 60022 records from Entomology Collection at the Natural History Museum of Utah. 1793 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 61 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 1 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 404 records from Symphyla Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 113451 records from ALCB - Herbário Alexandre Leal Costa. 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 3184 records from Herbarium specimens of Limoges university (LIMO). 4847 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 94857 records from Fish specimens of Kagoshima University Museum. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 297 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 233 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 7125 records from UTEP Invertebrates (Arctos). 11 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 2278 records from Mammals in MZNA-VERT: project Human impacts in rivers of Navarra. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 107 records from Range table from benthic foraminifers in ODP Hole 172-1061C. 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 44 records from Revision and phylogeny of Hypotelus Erichson: a Neotropical genus of minute rove beetles (Coleoptera, Staphylinidae, Piestinae). 4 records from Four new species of terrestrial-breeding frogs of the genus Phrynopus (Anura: Terrarana: Craugastoridae) from Río Abiseo National Park, Peru. 998 records from Korean Ethnobotany Database. 163 records from Relative abundance of coccosphere-units at site GIK23414. 521 records from Tentaculata collection of National Museum of Nature and Science. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 9220 records from Mollusca specimens of Ryukyu University Museum (Fujukan). 481 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 582 records from Herbarium Collections of the Centre for Plant Medicine Research (CPMR), Ghana. 41 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 833709 records from AMNH Bird Collection. 23643 records from CNIN/Abejas de México/Apoidea. 1567 records from Flora útil del Municipio de la Huerta, Jalisco. 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 4 records from Evidence for the continued presence in New Zealand of Homotrysis macleayi (Borchmann, 1909) (Coleoptera: Tenebrionidae: Alleculinae). 1726 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 6 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 689 records from BioBlitz Barcelona 2010-14. 5890 records from Rutgers University, Chrysler Herbarium - Macroalgae Collection. 43 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 302 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 21 records from Revision of the species related to Lalagetes subfasciatus Boheman and transfer of remaining Lalagetes species to other genera of Embrithini (Coleoptera: Curculionidae: Entiminae). 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 116446 records from Naturalis Biodiversity Center (NL) - Crustacea. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 12147 records from Danish Ants (Formicidae). 25 records from Brown algae specimens of Komatsu City Museum. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 5 records from Ecological Guild Evolution and the Discovery of the World’s Smallest Vertebrate. 39700 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 101 records from Component analysis of TV-guided grab sampler GeoB10071-5. 13 records from New records of mosquitoes (Diptera: Culicidae) found in phytotelmata in Northern Argentina. 22 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 798 records from Computarización de la Colección de Referencia de Nemátodos Fitopatógenos del Centro Nacional de Referencia Fitosanitaria de la Dirección General de Sanidad Vegetal. 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 25098 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 59 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 207 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 31 records from Two new species of the genus Narcotica Sugi, 1982 (Lepidoptera: Noctuidae: Acronictinae). 1667 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 27 records from (Table S2) Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 161-975D. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1810 records from The Broward College Insect Collection. 27324 records from Radiolaria specimens from the Norwegian Sea and Arctic Ocean. 19 records from Distribution Data for Megachile chomskyi. 23552 records from Berea College, Ralph L. Thompson Herbarium. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 175 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 3 records from Schwanseepark (87645 Schwangau). 3 records from A new species of Xiphogramma Nowicki (Hymenoptera: Chalcidoidea) from Saudi Arabia. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 139383 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 597 records from Eriophyoid Mites of Poland. 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 5 records from On the genus Aphaobius Abeille de Perrin, 1878, with description of a new species from the mesovoid shallow substratum (MSS) of Austria (Coleoptera: Leiodidae: Cholevinae: Leptodirini). 2 records from Neotype Designation for Aedes (Stegomyia) albopictus (Skuse). 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 1 records from Taxonomic re-evaluation of the monotypic genus Pararhabdophis Bourret, 1934 (Squamata: Colubridae: Natricinae) with discovery of its type species, P. chapaensis, from China. 1 records from On the Chilopoda from Turkey. 155 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 3 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 26 records from Genus Bungona Harker, 1957 (Ephemeroptera: Baetidae) from China, with descriptions of three new species and a key to Oriental species. 955 records from Vertebrados terrestres de San Juan de Camarones, Durango. 142 records from Botanical collection of the National Museum. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 24 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 24370 records from Muséum d'Avignon. 626 records from Mycology collection, Norwegian Forest and Landscape Institute. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 303 records from National Botanic Garden Belgium - Martius. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 2808 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 43 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 8328 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 173 records from UWIZM Anoles. 218 records from West African pholcid spiders: an overview, with desriptions of five new species (Araneae, Pholcidae). 11 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Nothrus pulverulentus. 34 records from The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 444 records from Pollen analysis of sediment profile TR0 from Truennensee. 526 records from FernsDarwinCore. 3 records from Überall ist Wunderland. 2451 records from Macrobenthos Chukchi Sea, 1986. 4269 records from Colección de hongos del Herbario "Jaime Andrés Rodríguez". LEB-Fungi. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 10 records from A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil. 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 24 records from A Gondwanan concept of Simplimorpha Scoble (sensu lato): a step toward clarity in the generic diagnostics of global Nepticulidae (Lepidoptera). 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 48 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 5 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 19 records from Revision of the Greater Antilles genus Paratrikona Spaeth, 1923 (Coleoptera: Chrysomelidae: Cassidinae: Dorynotini). 481 records from (Appendix B) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-966B. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 14 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 54 records from Nannofossil abundance of Hole 49-409. 20627 records from Herbier Louis-Marie (QFA) - Collection de lichens. 73 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 2 records from Two new species of Amphinemura (Plecoptera: Nemouridae) from Tibet. 1 records from A new species of Cyphocarididae (Crustacea, Amphipoda, Lysianassoidea) from off the northeastern Brazilian coast. 8 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 28468 records from Actualización de la base de datos del estado de Morelos de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 607514 records from Plant. 24 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 120 records from Pollen profile 2 from Richland Creek. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 13162 records from Observations du Conservatoire botanique national du Bassin parisien.. 177 records from Echinodermata specimens of Kuroshio Biological Research Foundation. 12859 records from Colecção Entomológica IIA. 17155 records from MZFC/Coleccion de Aves. 3426 records from Fossil Birds. 110350 records from TNHC Herpetology Collection. 83 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 110 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 4681 records from Museu Darder de Banyoles. 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 316 records from Moss species from Heard Island, 1987 and 2000. 818 records from floraregional_2da. 6941 records from DMNS Egg Collection (Arctos). 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 1421 records from Geochemistry and sedimentology on core POS200/10_6-2. 146 records from Colección de moldes endocraneanos del CENPAT. 14923 records from Lepidopterous specimens of Yamagata Prefectural Museum. 20 records from Biting midges of the tribe Ceratopogonini (Diptera: Ceratopogonidae) from the Middle East, with keys and descriptions of new species. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 7 records from The larva and pupa of Potamyia flavata (Banks 1934) (Trichoptera: Hydropsychidae): Description, life cycle, and notes on its biology. 1 records from Hornmilben (Oribatida) [pages 261 to 322]. 2 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Orthoptera - SMF. 54 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 2 records from Re-evaluation of the morphology of the monotypic genera Lycastonereis Rao, 1981 and Ganganereis Misra, 1999 (Annelida, Phyllodocida, Nereididae). 1121 records from Collection Meebold HBG Herbarium. 239 records from Hidden in plain sight: reassessment of the pig-footed bandicoot, Chaeropus ecaudatus (Peramelemorphia, Chaeropodidae), with a description of a new species from central australia, and use of the fossil record to trace its past distribution. 7 records from Cyphocharax boiadeiro, a new species from the upper rio Araguaia, Amazon basin, Brazil (Characiformes: Curimatidae). 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1 records from First fossil Eccoptarthridae (Coleoptera: Curculionoidea) from the Mesozoic of China. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 1702 records from BioGIS - Bryophytes - HUJ collections. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 4591 records from WII Herbarium Dataset. 1889 records from Diatomeas bentónicas de los oasis de Baja California Sur. 26309 records from Quaid-i-Azam University Herbarium. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 7270 records from COLETA - IMAR/DOP-Uac reference collection from 1977 to 2012. 2 records from A new species of cascade frog (Amphibia: Ranidae) in the Amolops monticola group from China. 1677 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 22 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 15 records from Université Pédagogique Nationale de Kinshasa- Les Insectes Comestibles de la R.D. Congo (Entomophagie). Projet CABIN (Central African Biodiversity Information Network). 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 9 records from Description of two new species of Magnispina and a new hypothesis of phylogenetic relationships for Heteropachylinae (Opiliones: Laniatores: Gonyleptidae). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 14 records from Species of Prioninae, Parandrinae, Lepturinae (Insecta, Coleoptera, Cerambycidae) and Disteniidae (Insecta, Coleoptera) from east Paraná State (Brazil), with three new geographic distribution records. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 2 records from The origin and evolution of the Tyrannosaurids, Part 1. 442 records from TAN_RUBIACEAE. 22 records from Thirteen new records of ferns from Brazil. 4 records from Bioacoustics and morphology of a new bush-cricket species of the genus Isophya (Orthoptera: Phaneropterinae) from Turkey. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 351 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 679 records from Collection Hydrozoa - ZSM München. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 202474 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 57198 records from FKSE-Herbarium of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 1 records from A new species of Marsipococcus Cockerell & Bueker (Hemiptera: Coccomorpha: Coccidae) from Malaysia. 6 records from Three new species of trigonopoid Platynotina (Tenebrionidae: Pedinini) from the Baviaanskloof Nature Reserve, South Africa. 1 records from Pritchardia boliviensis N. Gen., N. Sp. (Anoplocephalidae: Linstowinae) a tapeworm from opossums (Didelphidae) in the yungas and lowlands of Bolivia and Atlantic forest of Paraguay. 4 records from Mycale (Aegogropila) antiae sp. nov. (Demospongiae; Poecilosclerida; Mycalidae) from Galicia (NW Iberian Peninsula). 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 4792 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 3 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 4049 records from Estudio taxonómico distribucional de los peces del estado de Chiapas, México. 1241 records from Vertebrate collections of the Department of Animal Biology and Conservation Sciences, University of Ghana. 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 80 records from The Pyraloidea (Lepidoptera) fauna of the woody savannah belt in Mali, West Africa. 408 records from Antarctic and SubAntarctic Ophiuroidea - MNA (Section of Genoa). 15 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 14 records from Distribution of planktic foraminifera of sediment core GIK23062-1 at stadium 5.5. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 725 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 1872 records from Herbier National de Guinée (HNG) (BID-AF2015-0066-REG). 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 651 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 6071 records from EDIT - ATBI in Gemer area (Slovakia). 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 78 records from Nannofossil abundance of Hole 27-259. 22053 records from UTEP Vertebrates. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 175 records from Nannofossil abundance of Hole 20-199. 2 records from AKG-Gelände (Bensheim). 509 records from Pollen analysis of sediment profile NMS0 from Neumühler See. 356 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 6 records from On the Chilopoda from Turkey. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 5 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 4926 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 6 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 3621 records from Millenium Seedbank (MSB). 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 156 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 16128 records from Colección Ictiológica del Instituto Alexander von Humboldt. 3 records from Ditylenchus sarvarae sp. n. (Tylenchina: Anguinidae) from Iran. 15 records from NOTE SU ALCUNE SPECIE DEL GEN. EUPOLYBOTHRUS DELLA FAUNA DI GRECIA (Chilopoda, Lithobiomorpha). 24 records from Revision of the Diplommatinidae (Gastropoda: Cyclophoroidea) from Java. 250277 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 1486 records from Crustacea ZMK. 1 records from New hosts and localities for species of Cancricepon Giard & Bonnier, 1887 (Isopoda: Epicaridea: Bopyridae) with description of two new species and comments on the relationship between Cancricepon and Trapezicepon Bonnier, 1900. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 5 records from The genus Eremiothrips (Thysanoptera: Thripidae) from China, with one new species. 10 records from Results of foraminifer and ostracode analyses of Hole 302-M0002A. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM-IEOMA. 1 records from Lebensraum Gesamtschule (Langerwehe). 9120 records from ICEL (Land - Invertebrates). 28793 records from UTEP Herpetology (Arctos). 16 records from Range table from benthic foraminifers in ODP Hole 177-1088B. 5 records from A New Species of Abbrosoga (Hemiptera: Fulgoroidea: Delphacidae), An Endemic Puerto Rican Planthopper Genus, with an Updated Checklist of the Delphacidae of Puerto Rico. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 2 records from Langes Tannen (Uetersen). 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 21 records from A new genus of Theraphosid spider from Mexico, with a particular palpal bulb structure (Araneae, Theraphosidae, Theraphosinae). 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 15 records from Conringia orientalis. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 6 records from New species and records of the pseudoscorpion genus Geogarypus (Pseudoscorpiones: Geogarypidae) from India, Sri Lanka and New Guinea. 1195 records from edibleinsects. 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 7300 records from VIT Herbarium - Mycotheca (The Natural History Museum of Álava). 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 19 records from A new species and new records of Oocyclus Sharp, 1882 (Coleoptera: Hydrophilidae) from Brazil. 159 records from Nannofossil abundance of Hole 67-499B. 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 3 records from The pseudoscorpion genus Verrucachernes (Pseudoscorpiones: Chernetidae) in the Indian region. 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 10072 records from Guadeloupe_Herbier. 1 records from Diagnosies provisoires de quelques espèces nouvelles de fourmis de Madagascar, récoltées par M. Grandidier.. 24 records from Four new species of Paranaitis Southern, 1914 (Phyllodocidae, Annelida) from southern and southeastern Brazil. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 5 records from A new species of Hemigrammus Gill 1858 (Characiformes: Characidae) from the upper Rio Negro, Amazon basin, Brazil. 17 records from Description of Brachymeria philornisae sp. n. (Hymenoptera: Chalcididae), a parasitoid of the bird parasite Philornis trinitensis (Diptera: Muscidae) in Tobago, with a review of the sibling species. 2 records from Naturgrundstück (Eutin). 12127 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 28 records from Korean Plant Virus Database. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 1877 records from Odonata de la huasteca potosina (insecta). 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 718 records from Inventario florístico de las Cactáceas del estado de Tamaulipas, México. 274563 records from R. L. McGregor Herbarium Vascular Plants Collection. 26568 records from LiquenCAT: Banco de datos de los líquenes de Cataluña. 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 339 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 5 records from A new species of Astyanax Baird & Girard (Characiformes: Characidae) from the upper rio Araguaia, Central Brazil. 21 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 2780 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 878 records from COA Bird Collection (Arctos). 479 records from CBS Bacteria Database. 6 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 211 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 20 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 10654 records from Bryophyte specimens of The Nagoya University Museum. 1860 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 34518 records from University of Guam Insect Collection. 22857 records from National Botanic Garden Belgium - Myxomycetes. 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 5 records from Description of a new subspecies of Talicada nyseus (Guérin-Méneville, 1843) from Hainan, China (Lepidoptera: Lycaenidae), with notes on the genus Talicada Moore, 1881. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 23 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 109 records from Nannofossil abundance of Hole 24-232. 31 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 1 records from Ueber eine noch nicht beschriebene Nothrus-Art. 3072 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 1 records from A new aberrant Doryctinae genus (Hymenoptera: Braconidae) from French Guiana. 1189 records from UWIZM Molluscs. 317211 records from CAS Herpetology (HERP). 42957 records from Butler University Friesner Herbarium (BUT). 255225 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 265 records from Nannofossil abundance of Hole 36-329. 4 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 11499 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 7 records from First records of Glaresidae (Coleoptera) in China, with the description of a new species from Inner Mongolia and Shaanxi. 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 23 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 1001 records from Naturhistorisches Museum Mainz, Botanical Collection. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 1 records from Roter Berg Werdau (Leubnitz). 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 1793 records from Herbarium BSG Lichenes. 6 records from Rhigonema naylae n. sp. (Rhigonematomorpha: Rhigonematidae) a new parasitic nematode from a Japanese polydesmid millipede (Polydesmida: Xystodesmidae). 3 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 22615 records from University of California Santa Barbara Invertebrate Zoology Collection. 17581 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 85277 records from University of Ghana - Ghana Herbarium. 2 records from Pseudaeginella telukrimau sp. n., a new species of caprellid (Crustacea: Amphipoda) from Malaysia. 405 records from DNA and Tissue Bank of the Natural History Museum of Denmark. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 1943 records from Pollen profile RAC20, Lake Racou, France. 3 records from Some new brachypterous cockroaches (Blattodea: Blaberidae: Epilamprinae) from the Philippines. 2 records from A new gastropod associated with a deep-sea whale carcass from São Paulo Ridge, Southwest Atlantic. 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10898 records from Inventario de Hymenóptera; parasítica en México. 520 records from (Appendix 1a) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber in the Holocene section of sediment core GeoTu_SL096. 3 records from A new species of the genus Cyparium from northern Sulawesi, Indonesia (Coleoptera: Staphylinidae: Scaphidiinae). 4639 records from UAM Herbarium (ALA), Algae Collection (Arctos). 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 22516 records from MfN - Fossil Fish Collection. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 58368 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 16 records from Endemism and long distance dispersal in the waterfleas of Easter Island. 91 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 36 records from Pseudolaguvia ferula, a new species of sisoroid catfish (Teleostei: Erethistidae) from India.. 23 records from Nannofossil abundance of Hole 24-233A. 3006 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 877 records from Sistemática y biogeografía del género Reithrodontomys (Rodentia: Muridae). 2 records from schulgarten. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 9 records from The identity of Aplocheilus andamanicus (Köhler, 1906) (Teleostei: Cyprinodontiformes), an endemic Killifish from the Andaman Islands, with notes on Odontopsis armata van Hasselt. 66 records from The Neotropical annual killifish genus Pterolebias Garman (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology, and taxonomic revision.. 77 records from Distribución del gecko introducido Hemidactylus frenatus (Dumeril y Bribon 1836) (Squamata: Gekkonidae) en Colombia. 217 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 3 records from Sinorhodeus microlepis, a new genus and species of bitterling from China (Teleostei: Cyprinidae: Acheilognathinae). 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 3425 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 3 records from One new species of the subgenus Xizicus (Zangxizicus) (Orthoptera: Tettigoniidae: Meconematinae) from China. 29 records from Herbarium Senckenbergianum (FR) - Protista. 116 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 13 records from The myth of monophagy in Paralobesia (Lepidoptera: Tortricidae)? A new species feeding on Cypripedium reginae (Orchidaceae). 1 records from Oribates humeralis. 175 records from PSUZC-Rodents Collection. 33 records from Checklist of rust fungi (Pucciniales) occurring in Portugal. 3 records from Zoology in the Middle East. 4 records from Two new species of Parandrinae (Coleoptera: Cerambycidae) in the genera Parandra and Acutandra from South America. 16258 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 12 records from Neoplasta Coquillett (Diptera: Empididae: Hemerodromiinae) from Brazil: new species and male description of N. fortiseta Smith. 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 1 records from First description of the male of Oxythrips tristis Bagnall (Thysanoptera: Thripidae). 21 records from The Oribatid Family Phthiracaridae III. Redescription of Phthiracarus nitens (Nicolet). 10 records from Echinodera (Ruteria) soumasi sp. n. from Greece (Coleoptera, Curculionidae). 822 records from (Table 1) Relative abundances of benthic foraminifera in ODP Hole 117-725C. 82 records from Osmiine bees of the genus Haetosmia (Megachilidae, Osmiini): biology, taxonomy and key to species. 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 11 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Echinodermata. 353 records from Benthic foraminifera accumulation rate and benthic foraminiferal productivity proxies at ODP Site 165-999 in the Caribbean (Appendix A). 5448 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 204 records from Echinoderms from the Seaflower Biosphere Reserve. 6 records from Gobiesox lanceolatus, a new species of clingfish (Teleostei: Gobiesocidae) from Los Frailes submarine canyon, Gulf of California, Mexico. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 16 records from Cryptic diversity in the Azorean beetle genus Tarphius Erichson, 1845 (Coleoptera: Zopheridae): An integrative taxonomic approach with description of four new species. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 22 records from Redescription of the genus Koumansetta (Teleostei: Gobiidae), with description of a new species from the Red Sea. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 1 records from First record of family Dipsocoridae (Hemiptera: Heteroptera: Dipsocoromorpha) from the Korean Peninsula and a new generic combination for Cryptostemma japonicum Miyamoto. 218 records from Nannofossil abundance of Hole 49-408. 25 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 278425 records from Allan Herbarium (CHR). 254268 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 26 records from Schwedische Oribatei (Acari). III.. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 2 records from Birkenloh. 1 records from Hypochthonius rufulus. 21 records from Nomenclatural changes and lectotype designations in the seed-beetle genus Sennius Bridwell: with the synonymization of Megasennius Whitehead & Kingsolver (Coleoptera: Chrysomelidae: Bruchinae). 18656 records from Coleção Entomológica Moure e Costa. 6 records from New records of benthic hydroids (Cnidaria: Hydrozoa) from the coast of Oaxaca, Mexico. 3 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 13 records from Taxonomic notes on genus Coelotrypes Bezzi (Diptera: Tephritidae: Trypetinae) with description of two new species. 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 3133 records from Collection Cnidaria fossil SMF. 2 records from NSG Karwendel. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 5 records from A new Oreonetides Strand, 1901 from the Russian Far East (Araneae, Linyphiidae). 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 7 records from Revision of the Afrotropical genus Susua Lugo-Ortiz & McCafferty 1998 (Ephemeroptera: Baetidae: Protopatellata). 79084 records from SA Flora (BDBSA). 5428 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 2 records from Warnowtal (Rostock). 19 records from Feather mites of the genera Dubininia and Cacatualges (Acari: Xolalgidae) associated with parrots (Aves: Psittaciformes) of the Old World. 7 records from A new genus of the mite family Scutacaridae (Acari: Heterostigmata) associated with Trinervitermes trinervoides (Isoptera: Termitidae) from South Africa. 39 records from A review of all Recent species in the genus Novocrania (Craniata, Brachiopoda). 1 records from Celaeno coccinea. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 27830 records from Marie-Victorin Herbarium (MT) - Bryophytes. 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 15 records from Free-living nematodes of the genus Syringolaimus de Man, 1888 (Nematoda, Enoplida, Ironidae) from the Angola Basin, South-East Atlantic Abyss. 3 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 1 records from A new species of the genus Humphaplotropis from China (Orthoptera: Pamphagidae, Pamphaginae). 1350 records from martius-munchen-infocomp. 181 records from Dinoflagellate cysts from sediment core PS1295-4. 9 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 186 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 7 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 8109 records from Fiocruz/CAVAISC - Coleção de Artrópodes Vetores Ápteros de Importância em Saúde das Comunidades. 14510 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 8704 records from HSU Wildlife Birds. 1371 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 2 records from Two new species of Aphelochaeta (Annelida: Polychaeta: Cirratulidae) from Korean waters. 4 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 3190 records from Utah State University, Intermountain Herbarium. 946 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 2998 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 4 records from Discovery of the first pincer wasp (Hymenoptera, Dryinidae) from Rovno amber. 10 records from Diglotta mersa (Haliday) and Halobrecta flavipes Thomson, two new species for the Canadian fauna (Coleoptera, Staphylinidae, Aleocharinae). 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 4 records from Arthropoden aus südostalpinen Höhlen.. 10 records from Plateurytion roigi sp. nov., a new geophilid centipede (Myriapoda: Chilopoda: Geophilomorpha) from Southern Chile. 887 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 2355 records from Colección Ictiológica del CENPAT-CONICET. 1287 records from Revision of Anisepyris Kieffer (Hymenoptera, Bethylidae), with description of 135 new species. 1 records from First finding of the shrimp genus Harperalpheus Felder & Anker, 2007 in the eastern Pacific, with description of a new species from Bahía Málaga, Colombia (Malacostraca: Decapoda: Alpheidae). 6 records from Three new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 246 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/046-3. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 7 records from Two new species of comb-clawed beetles (Coleoptera: Tenebrionidae: Alleculinae) from Yunnan, China. 2 records from An enigmatic new genus of cyclostome braconid wasp (Hymenoptera: Braconidae) from New Zealand. 17 records from Fossil and Recent molluscan types in the Auckland War Memorial Museum. Part 2: Polyplacophora and Scaphopoda. 2799 records from University of Sindh Jamshoro Herbarium. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 266 records from Revision of the genus Doryscus Jacoby (Coleoptera: Chrysomelidae: Galerucinae). 31 records from New species and records of Cladiopsocus Roesler (Psocodea: ‘ Psocoptera’: Psocomorpha: Cladiopsocidae) from Colombia. 77 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 16 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 41 records from Registros Primates Neotropicales Convocatoria APC. 161 records from A conspectus of the native and naturalized species of Nephrolepis (Nephrolepidaceae) in the world. 3110 records from Herpetile collection NTNU University Museum. 3 records from Taxonomic review of the genus Urostylis (Hemiptera: Heteroptera: Urostylididae) from the Korean Peninsula, with description of a new species. 3002 records from Colección de Peces Universidad Católica de Oriente. 19 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 1274 records from Fitoplancton marino frente a Baja California. 2. Áreas de surgencias de la región Ensenadense. 581 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 362 records from The genus Sphecodes Latreille 1804 (Hymenoptera: Apoidea: Halictidae) in Central Asia. 45811 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 14573 records from Biological Reference Collections ICM CSIC. 245 records from A review of Tersilochinae (Hymenoptera: Ichneumonidae) of Finland. Part 1: taxonomy. 6 records from First Record of Dericorys albidula Serville, 1838 (Orthoptera: Dericorythidae) in Tunisia and Libya. 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 349178 records from AMNH Herpetology Collections. 18094 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 2568 records from Fish (NHMK-PI). 127499 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 3 records from Urwald 1 (Bad Waldsee). 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 174 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 834 records from Nannofossil abundance of Hole 74-526A. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 8 records from Description of the helminth communities of sympatric rodents (Muroidea: Cricetidae) from the Atlantic Forest in northeastern Argentina. 378 records from Ichthyologie ZMK. 99 records from G.B. Pant Institute of Himalayan Environment & Development - Plants of West Himalaya, India. 12 records from Description of a new Aemene Walker, 1854 from North Thailand and Myanmar, with a checklist of the genus (Lepidoptera, Erebidae, Arctiinae). 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 34 records from A New Species Of Apostenus From California, With Notes On The Genus (Araneae, Liocranidae). 844 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 1 records from New genus and species of the family Niphargidae (Crustacea: Amphipoda: Senticaudata), Chaetoniphargus lubuskensis gen. nov., sp. nov. from Croatia. 13 records from A new species and a key to world species of the flavipes species-group of the genus Cotesia Cameron, 1891 (Hymenoptera: Braconidae: Microgastrinae) from Japan. 220 records from Mammals in MZNA-VERT: project Loza. 5 records from A revision of the genus Saccoglossus (Hemichordata: Enteropneusta: Harrimaniidae) with taxonomic descriptions of five new species from the Eastern Pacific. 5 records from New species of the snakefly genus Mongoloraphidia (Raphidioptera: Raphidiidae) from China. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 68 records from Nannofossil abundance of Hole 73-521A. 27 records from Taxonomic study of the genus Promalactis Meyrick (Lepidoptera, Oecophoridae) from Hainan Island, China (III). 1798 records from Insect (KIDR-IN). 635 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 1 records from A new generic name, Semigothograptus, for Gothograptus? meganassa Rickards & Palmer, 2002, from the Silurian post- lundgreni Biozone recovery phase, and comparative morphology of retiolitids from the lowermost upper Homerian (upper Wenlock). 27 records from An annotated checklist and key to the Bulgarian cockroaches (Dictyoptera: Blattodea). 10 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-129BX. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 2864 records from E. C. Smith Herbarium (ACAD) - Cape Breton University Collection. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 4 records from Critical Checklist of the Indian species of Hypogastrura (Collembola: Hypogastruridae) with a description of a new species from Satkosia Wild Life Sanctuary. 20 records from New records for Albania based on taxa from the Prespa National Park. 115 records from Mammalians Specimens of Akita Prefectural Museum. 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 4 records from Description of a new Oriental stonefly species, Phanoperla constanspina (Plecoptera: Perlidae) from Mindanao, Philippines and association of life stages using DNA barcoding. 5 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 6723 records from Los mamíferos del estado de Durango, México. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 7 records from New species of Xiphoniscus and new record of Androdeloscia escalonai (Isopoda, Scutocoxifera, Oniscidea, Philosciidae) from Brazilian Amazon. 14 records from A taxonomic review of the genus Acanella (Cnidaria: Octocorallia: Isididae) in the North Atlantic Ocean, with descriptions of two new species. 103 records from Distribution of planktonic foraminifera of sediment core SH1972_10. 99071 records from MSB Fish Collection (Arctos). 47 records from Two new species of Oxynoemacheilus from the Tigris drainage in Iraqi Kurdistan (Teleostei: Nemacheilidae). 134 records from Pollen record of profile 3TZ2. 18 records from Aves de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 11 records from A taxonomic revision of the genus Thalia Blumenbach, 1798; Weelia Yount, 1954; Brooksia Metcalf, 1918 (Salpida: Salpidae) from East Coast of Peninsular Malaysia. 1 records from The genus Alphocoris in the Indomalaya (Hemiptera: Heteroptera: Scutelleridae). 11732 records from Ecología y biogeografía de epífitas vasculares de Chiapas, México. 1 records from Hoplophora ardua. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 5 records from New species of the non-biting midges of Tribe Chironomini (Dptera, Chironomidae) from the Bolshekhekhtsyrsky Reserve (Russia, Khabarovsk Territory). 4 records from Two new species of Podonomus Philippi (Diptera: Chironomidae: Podonominae) from mountains of Southeastern Brazil. 216 records from Ecología e historia natural de Schistocerca americana socorro y S. piceifrons piceifrons en Isla Socorro. 106 records from Coloration variability of the Oriental genus Agnorimus Miyake & Iwase, 1991 (Coleoptera: Scarabaeidae, Cetoniinae) with synonymic notes. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 37986 records from rmca-albertine-rift-cichlids. 62 records from Revision of the Madagascan genera Oncodopus Brongniart and Colossopus Saussure (Orthoptera: Tettigoniidae: Conocephalinae; Euconchophorini), with description of Malagasopus gen. nov.. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 7128 records from La familia Asclepiadaceae en México. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 18 records from Six new species of Otacilia from southern China (Araneae: Phrurolithidae). 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 377 records from Diatom abundance measured on water bottle samples at station PS58/043-2. 579 records from Pollen analysis of sediment profile KR0 from Kreutzsee. 6 records from First description of the male caste of the Himalayan endemic ant Lasius alienoflavus Bingham, 1903 (Hymenoptera: Formicidae), with re-description of the female and queen castes. 307 records from Type Localities of Heteroptera (Insecta: Hemiptera) from Turkey. 1490 records from Donación de la base de datos del Dr. Ortega Paczka resultados de la computarización de datos de colecta de muestras de maíz y otros cultivos asociados de diferentes regiones de México. 464 records from Bocachico Prochilodus magdalenae (Characiformes: Prochilodontidae) en la cuenca media y baja del río Magdalena. 3 records from Helobdella buzz n. sp. (Clitellata: Hirudinida), a bromeliad leech from the Brazilian Atlantic Forest. 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 421 records from Sistemática del género Polianthes L (Agavaceae). 1889 records from Ims fish tag database. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 15000 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 286 records from Catalogue of the primary types of marine molluscan taxa described by Tommaso Allery Di Maria, Marquis of Monterosato, deposited in the Museo Civico di Zoologia, Roma. 55 records from Three new species of Ametadoria Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, Costa Rica. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 12 records from The first record of Gnathostenetroididea Kussakin, 1967 from Australian waters with description of four new species of Gnathostenetroides Amar, 1957 (Crustacea: Isopoda: Asellota) from the Great Barrier Reef. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 404842 records from Texas A&M University Insect Collection. 4 records from New information on the skipper fauna of Guangxi, China (Lepidoptera, Hesperiidae). 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 2739 records from Palynological investigation of profile Tso Kar. 10000 records from Herbarium of Shinshu University. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 383 records from Nannofossil abundance of Hole 66-490. 4400 records from USAC Mammals Collection. 2442 records from Foraminifera, sedimentological parameters and sea surface temperature and salinity calculated on core SO82_5-2. 349458 records from KUBI Herpetology Collection. 6 records from The uncommon Neotropical genus Pazius Navás, 1913 (Mecoptera: Bittacidae): a comprehensive synthesis, with description of a new Brazilian species. 5 records from A new genus and species of Neotropical Nemobiinae (Insecta: Orthoptera: Grylloidea: Trigonidiidae: Nemobiinae). 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 218 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 6104 records from SMNS Palaeontological collection - Amber and fossil insects. 9 records from World’s northenmost and rarely observed Nudibranchs: three new Onchidoridid species (Gastropoda: Doridida) from Russian seas. 1 records from Redescription of the poorly known pea crab, Pinnixa plectrophoros Glassell, 1935 (Decapoda: Pinnotheridae), from the Gulf of California. 2 records from Two new species of Biantes from China and Malaysia (Opiliones: Laniatores: Biantidae). 8 records from First report of the genus Phytodietus Gravenhorst, 1829 (Hymenoptera: Ichneumonidae: Tryphoninae) from Thailand. 363 records from PSUZC-Reptile Collection. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1136 records from Nannofossil abundance of Hole 82-558A. 5 records from A new monotypic genus, a species synonymy and nomenclatural corrections in the arid-adapted Canthonini (Scarabaeidae, Scarabaeinae) from the Succulent Karoo Biome of south-western Africa. 1513 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 1 records from Collection Quaternary Small Mammals IQW. 29 records from Revision of the enigmatic Southeast Asian spider genus Savarna (Araneae, Pholcidae). 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 155 records from The genus Tarsonemus Canestrini and Fanzago, 1876 (Acari: Heterostigmatina: Tarsonemidae) in East Azerbaijan, Iran, with a description of T. lenticulatus sp. nov. and re-description of T. annotatus Livshits, Mitrofanov and Sharonov, 1979. 17 records from A molecular phylogeny of Speonemadus Jeannel, 1922 with description of two new species from Morocco (Coleoptera: Leiodidae: Cholevinae: Anemadini). 6873 records from Monitoring of the intertidal biodiversity of rocky beaches with schools in Portugal 2005-2010. 350 records from Nannofossil abundance of Hole 59-448. 8 records from Gergithoides Schumacher, 1915 in Vietnam, with two new species, and taxonomic notes on the genus (Hemiptera: Fulgoromorpha: Issidae). 4 records from First report of the genus Tettigonia Linnaeus (Orthoptera: Tettigoniidae: Tettigoniinae) and record of Tettigonia caudata caudata (Charpentier, 1842) from India. 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 121 records from Nannofossil abundance of Hole 7-63A. 58 records from The mutillid wasps of the Dasymutilla paradoxa species-group (Hymenoptera, Mutillidae). 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 30985 records from MEXU/Asteraceae. 5640 records from Collection Echinodermata SMF. 122 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 232661 records from Oklahoma Vascular Plants Database Provider. 350 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 25 records from Annotated checklist of the fishes of the archipelago of Madeira (NE Atlantic): I-Chondrichthyes. 1 records from A new species of the Australian genus Clinopsocus New from coastal California (Psocodea: ‘ Psocoptera’: Elipsocidae). 740 records from Targeting a portion of central European spider diversity for permanent preservation. 10907 records from Census of species recorded during phytosociological surveys in Benin. 794 records from Studies in Hawaiian Diptera III: New Distributional Records for Canacidae and a New Endemic Species of Procanace. 91 records from Number of live benthic foraminifera in Nordensheld Bay, Novaja Zemlja. 8 records from New Hemilophini, Aerenicini and Calliini from French Guiana, transference and notes on Hemilophini (Coleoptera, Cerambycidae, Lamiinae). 53 records from Squid collection from 1995/96 V4 BROKE. 439 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 126 records from Programa para la Conservación Integral de Diez Especies de Plantas Prioritarias del BST. 11 records from New species of Dichogaster Beddard, 1888 (Clitellata: Benhamiidae) with additional records of earthworms from Guadeloupe (French West Indies). 98 records from The genus Pholetesor Mason, 1981 (Hymenoptera, Braconidae, Microgastrinae) from China, with descriptions of eleven new species. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 150 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 23 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part II. Genus Bradysiopsis Tuomikoski, 1960. 67 records from (UTCR) University of Tennessee - Reptiles Collection. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 1 records from Artensuche auf den Elbwiesen in Radebeul. 6 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 651 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 28385 records from Collection Pisces SMF. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 1 records from Oribates punctum. 13 records from A new species of Soikiella Nowicki (Hymenoptera: Trichogrammatidae) from Italy. 8980 records from MEXU/Tipos de plantas vasculares. 56 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1642 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 4 records from Revision of the family Carabodidae (Acari: Oribatida) V (Fifth part). Redescription of Congocepheus latilamellatus Mahunka 1984, with complementary studies of C. ornatus, Mahunka 1983. Descriptions of Tanzaniacepheus gen. nov. and Zimbabwecepheus gen. nov.. 13 records from Bryozoa of the British Isles. 331 records from Administración Nacional de Institutos y Laboratorios de Salud. 23 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 356 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 1447 records from (Appendix 2-7) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 59-451 in the western Pacific Ocean. 1 records from Cuxhavener Küstenheiden. 255 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/043-2. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 80123 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 2393 records from UWYMV Bird Collection (Arctos). 11994 records from Hatikka Observation Database. 1000 records from Diplopoda (JJHA-DI). 2 records from Wiesenbiotop am Wasserturm. 20 records from A new species of sardine, Sardinella electra (Teleostei: Clupeiformes: Clupeidae), from the Ryukyu Islands, Japan. 200187 records from inatura - Erlebnis Naturschau Dornbirn. 17228 records from CAS Entomology Type (TYPE). 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 103178 records from MfN - Heteroptera Collection. 354 records from Sponges of the Guyana Shelf. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2020 records from Birds (NHMK-BI). 2476 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 11551 records from MBML-Anfibios - Coleção de Anfíbios MBML. 119 records from Kinorhyncha. 2 records from Myrmica afghanica (Hymenoptera: Formicidae), a new ant species from Afghanistan.. 1618 records from Dataset of herbarium specimens of threatened vascular plants in Catalonia. 1 records from A new genus of the Tympanophorus lineage of the subtribe Anisolinina from Madagascar (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 140 records from The Oncometopia orbona species group (Hemiptera, Cicadellidae, Proconiini). 16 records from A new species of Tropidophorus Duméril & Bibron, 1839 (Squamata: Sauria: Scincidae) from Sarawak, East Malaysia (Borneo). 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 15760 records from CHAS Ornithology (Arctos). 6 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 4 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 11584 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 5 records from Two new species of the genus Unaspis MacGillivray, 1921 (Hemiptera: Coccomorpha: Diaspididae) from China. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 173 records from Barcant Butterfly Collection - Papilionidae. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 107580 records from Database of invertebrates collected in Mongolia. 3 records from New data of Nazeris Fauvel in Xizang, China (Coleoptera, Staphylinidae, Paederinae). 4 records from Taxonomic updates for some confusing Micronesian species of Camponotus (Hymenoptera: Formicidae: Formicinae). 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 18 records from Two new species and key to the salina group of the genus Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) from Colombia. 10075 records from Nematoda of Costa Rica (INBio). 32916 records from Insect specimen database of Atsugi City Museum. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 4 records from A new Puddle Frog, genus Phrynobatrachus (Amphibia: Anura: Phrynobatrachidae), from the eastern part of the Upper Guinea biodiversity hotspot, West Africa. 4 records from Description of four new species of the Cirolana ‘ parva group’ (Crustacea: Isopoda: Cirolanidae) from Thailand, with supporting molecular (COI) data. 177 records from Nannofossil abundance of Hole 30-285A. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 170 records from The taxonomic history of Indo-Papuan groundsnakes, genus Stegonotus Duméril et al., 1854 (Colubridae), with some taxonomic revisions and the designation of a neotype for S. parvus (Meyer, 1874). 444 records from (Appendix 3) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD99-2341. 1 records from VANILLA RIVASII (ORCHIDACEAE), A NEW SPECIES FROM THE COLOMBIAN PACIFIC REGION. 9 records from Three new species of the Stenus cephalotes group fom Zhejiang, East China (Coleoptera, Staphylinidae). 7242 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 6 records from Review of the genus Cruziohyla (Anura: Phyllomedusidae), with description of a new species. 607 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 213 records from Pollen record of profile 3TZ. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 373028 records from South Australian Museum Australia provider for OZCAM. 1 records from Regionalpark(Hattersheim). 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 131 records from Foraminifera abundance of sediment core BM1958.631. 425 records from Nannofossil abundance of Hole 30-285. 26 records from A new species of Phrynus Lamarck, 1801 (Arachnida: Amblypygi), from Trinidad and Tobago, and Venezuela, with a redescription of Phrynus pulchripes (Pocock, 1894). 100 records from Brock University Herbarium (BU). 148 records from Herbarium BSG Hepaticopsida. 1 records from Description of the last stadium larva of Erythrodiplax abjecta (Anisoptera: Libellulidae) from the eastern Colombian Andes. 150 records from Museu Paraense Emílio Goeldi - Crocodylia Collection. 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 82855 records from Museu Paraense Emílio Goeldi - Ornithology Collection - Skin. 9 records from New data on the genus Syndicus Motschulsky (Coleoptera: Staphylinidae: Scydmaeninae) from Yunnan, southern China. 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 22 records from Collection Mantodea - SMF. 1201 records from Monocotyledonous Geophytes of Fergana Valley. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 86 records from UWIZM Cnidarians. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 798 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from A new species of the spider genus Solenysa from China (Araneae, Linyphiidae). 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 11 records from New records and a new species of bivalve (Mollusca: Bivalvia) from Miocene hydrocarbon seep deposits, North Island, New Zealand. 6 records from On the systematics of the water mites Hygrobates nigromaculatus Lebert, 1879 and H. setosus Besseling, 1942 (Acari, Hydrachnidia, Hygrobatidae). 87279 records from Taiwan Forestry Research Institute. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 92 records from A list of coleoptera recorded in Mixed Forest habitat in Arabuko-Sokoke Forest, Kenya. 31229 records from DIPOL. 14660 records from MfN - Fossil invertebrates IIb. 323 records from CNAN/Pseudoscorpiones. 1800 records from Colección Zoológica de la Universidad del Tolima (CZUT)- Mastozoología. 152102 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40173 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 20287 records from UAM Invertebrate Collection (Arctos). 18 records from The genera and species of Comatulidae (Comatulida: Crinoidea): taxonomic revisions and a molecular and morphological guide. 8 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 1284 records from Collection of Heteroptera. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 2 records from Landschaftspflegehof (Berlin). 1 records from Bachpatenschaft Beeke. 815 records from Listado taxonómico de la ictiofauna de la costa de Michoacán. 7 records from A new species of Alonella Sars, 1862 (Crustacea: Cladocera: Chydoridae) from the Ecuadorian Andes. 122 records from Checklist of Cerambycidae (Coleoptera) primary types of the Coleção Entomológica Pe. Jesus Santiago Moure, Departamento de Zoologia, Universidade Federal do Paraná, Curitiba, Paraná, Brazil, Instituto Nacional de Pesquisas da Amazônia, Amazonas, Manaus, Brazil, and of the Museu Paraense. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 176 records from A checklist of the Robber Flies (Insecta: Diptera: Asilidae) of Wyoming, USA. 28187 records from UAZ Mammals. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 2 records from Artenvielfalt auf den Elbwiesen (Dessau). 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 40 records from Geothermal Fumarole Subsurface Mt. Erebus, Antarctica. 2723 records from Actualización de la base de datos de colémbolos de México. 2917 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 8 records from Order Diptera, family Mydidae. 336 records from Malawi-Saturniidae-Biodiversity-Data. 35 records from Coccoliths in sediment core PS1295-4. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 245 records from Bird specimens of Obihiro Centennial City Museum. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1799 records from Catálogo de los mamíferos de México en resguardo de The Natural History Museum (London), Inglaterra. 79 records from Estructura genética poblacional de las especies de Tapaojitos (Aves Parulinae: Geothlypis) que ocurren en los humedales de México: Uno de los hábitats más amenazados de nuestro país. 57022 records from Fish Specimens. 25 records from New species of Chimaera (Chondrichthyes: Holocephali: Chimaeriformes: Chimaeridae) from the Southwestern Indian Ocean. 17713 records from NCSM Mammals Collection. 6234 records from SMNS Palaeontological collection - Amphibians, reptiles (Palaeozoic, Mesozoic). 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 9 records from Distribution of planktic foraminifera of sediment core GIK23352-3 at stadium 5.5. 1 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 1 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 26 records from Akysis longifilis, a new species of catfish (Teleostei: Akysidae) from Myanmar.. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 38127 records from VIC - Herbário da Universidade Federal de Viçosa. 76262 records from Colección de Entomología del Instituto Alexander von Humboldt. 7 records from FIRST REPORT OF THE GENUS SESIEUTES SIMON (ARANEAE: LIOCRANIDAE) FROM CHINA, WITH DESCRIPTION OF ONE NEW SPECIES. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 2 records from Rediscovery of the holotypes of Mustela africana stolzmanni Taczanowski, 1881 (Carnivora: Mustelidae) and Cuniculus taczanowskii Stolzmann, 1885 (Rodentia: Cuniculidae) at the Museum and Institute of Zoology Polish Academy of Sciences in Warsaw, Poland. 377 records from Hydraenidae of Madagascar (Insecta: Coleoptera). 1 records from On the Chilopoda from Turkey. 179947 records from Arctic Ocean Diversity. 13 records from The dacnusine genus Chorebus Haliday (Hymenoptera: Braconidae: Alysiinae) from China. 2 records from New species of cynipid inquiline, Saphonecrus kuriphilusi (Hymenoptera: Cynipidae: Synergini), from Dryocosmus kuriphilus galls in Greece. 4207 records from CASES2003_2004. 697 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 3 records from Nouvelles fourmis de Madagascar.. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 122 records from A second update to the checklist of Finnish long-legged flies (Diptera: Dolichopodidae), with a re-evaluation of the status of Hydrophorus callosoma Frey, 1915. 151 records from CHAS Botany Collection (Arctos). 32 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 95 records from Código de barras de diferentes grupos de peces mexicanos endémicos de la Mesa Central Mexicana. 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 5 records from A new species of Contarinia (Diptera: Cecidomyiidae) damaging inflorescence of Carya cathayensis (Juglandaceae) in China. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 1807 records from Données d'occurrence de la flore du Sénégal (Acanthaceae - Chenopodiaceae), Herbier IFAN. 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 3 records from Naturschutzgebiet Lochbusch-Königswiesen. 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 12 records from Three new species of Seira Lubbock (Collembola, Entomobryidae, Seirinae) from Madagascar with Lepidocyrtus - like habitus. 7814 records from Odonata de Veracruz. 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8 records from A review of the genus Paratus Simon (Araneae, Dionycha). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 4 records from Four new species of tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) from the Afrotropical Region. 3 records from New European records of Ditomyia macroptera Winnertz (Diptera: Ditomyiidae) with notes on its distribution. 6 records from Three new species of Calyptotheca (Bryozoa: Lanceoporidae) from the Great Barrier Reef, tropical Australia. 1 records from A new mesoserphid wasp from the Middle Jurassic of northeastern China (Hymenoptera, Proctotrupoidea). 11 records from Notes on Onciderini (Coleoptera, Cerambycidae, Lamiinae): description of a new species of Lesbates Dillon & Dillon and new distribution records. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 5 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 45180 records from Collection Herpetology SMF. 1 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 17 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 6393 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 1 records from A new species of Tyrannomyrmex (Hymenoptera: Formicidae: Myrmicinae) from India.. 352692 records from Plantae of Costa Rica (INBio). 600 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 1 records from Nothrus runcinatus. 56942 records from Annelida collection of National Museum of Nature and Science. 14 records from Walldorf-Wiesloch: "Natur über den Gleisen". 2 records from The webspinning sawfly genus Neurotoma (Hymenoptera, Pamphiliidae) of South Korea: Neurotoma silla sp. nov. and a key to species. 1 records from A new species of Macrosaccus (Lepidoptera: Gracillariidae: Lithocolletinae) from Arizona, USA. 1 records from Myriopoden von Kreta, nebst Bitraegen zur allgemeinen Kenntnis einger Gattungen. 5 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 55 records from Review of the Priocnemis hyalinata species-group (Hymenoptera: Pompilidae), with description of a new species from China. 11686 records from Escarabajos coprófagos (Coleoptera: Scarabaeidae: Scarabaeinae) de bosques secos Colombianos de la Colección Entomológica del Instituto Alexander von Humboldt. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 516 records from Range table from benthic foraminifers in ODP Hole 172-1055C. 494 records from Análisis de Integridad Biológica para el Parque Natural Regional Páramo del Duende. Convenio CVC- Univalle 108 de 2017. 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 26 records from A new tarantula species from northern Australia (Araneae, Theraphosidae). 3 records from New synonym of Tipula (Vestiplex) wahlgrenana Alexander, 1968 (Diptera: Tipulidae). 449 records from Wichita State University Collection. 595 records from La liste (3) Rouge des plantes menacées de la Guinée. 2 records from Am Moosangerweg. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 647 records from pbzt_insect_biodiversity. 62283 records from PRECIS (KwaZulu-Natal Herbarium). 7 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 281 records from NZCS Upper Tapanahony Expedition 1991. 1 records from Oppia nitens. 15 records from Contribution to the Chinese Rhaphidophorinae Walker, 1869 (Orthoptera: Rhaphidophoridae: Rhaphidophorinae): New species of Rhaphidophora Serville, 1838 from China. 24 records from Tanzanian Vertebrate Collection. 10 records from New species of Callichromatini Swainson, 1840. (Coleoptera, Cerambycidae). New Cerambycidae from Vietnam. Part 6. 41 records from Support for the underrepresented sex: new descriptions of scutacarid males (Acari, Heterostigmatina). 2 records from A new Neotropical genus of bee flies (Diptera, Bombyliidae, Phthiriinae). 1 records from Kohlbach (Sulzfeld). 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 77 records from Terrestrial isopods of the genus Porcellio Latreille, 1804 (Isopoda; Oniscidea) in Iran, with a description of a new species. 603 records from Fossil (NSMK-FO). 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 9902 records from DSMZ Bacteria. 247497 records from CAS Entomology (ENT). 4126 records from Naturalis Biodiversity Center (NL) - Pisces. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 106 records from Nannofossil abundance of Hole 74-526C. 2425 records from Ichneumonidae (Hymenoptera) de la reserva de la biosfera El Cielo, Tamaulipas. 8373 records from PACA-Bryophytes - Herbarium Anchieta - Aloysio Sehnem. 386 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 320 records from Myxomycetes collection of the University of Eastern Finland. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 70 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 4 records from Pycnogonidea specimens of Kuroshio Biological Research Foundation. 2 records from Two new Opadometa species (Araneae: Tetragnathidae) from Sarawak, Malaysia. 15 records from Discontinuous color variation in the assassin bug species Tiarodes miyamotoi (Hemiptera: Reduviidae: Reduviinae). 13 records from The discovery of Lepidocyrtoides Schött, 1917 (Collembola, Entomobryidae, Entomobryinae) from the New World, including three new species from Brazil and one from Australia. 1 records from Mites of the family Parasitidae Oudemans, 1901 (Acari: Mesostigmata) from Japan: a new species of Vulgarogamasus Tichomirov, 1969, and a key to Japanese species. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 5582 records from Riqueza de especies y biodiversidad edáfica de una zona de humedales del Parque Nacional Arrecife de Puerto Morelos, Quintana Roo, México. 14009 records from Collection Trichoptera - SMF. 2 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 235 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 1 records from Geographically structured genetic variation in Ptychozoon lionotum (Squamata: Gekkonidae) and a new species from an isolated volcano in Myanmar. 14842 records from CSIC-Real Jardín Botánico-Colección de Líquenes (MA-Lichen). 5 records from Pseudonemesia tabiskey, a new species of Pseudonemesia Caporiacco 1955 and new ultramorphological data for the Microstigmatinae (Araneae: Microstigmatidae). 119 records from Distribution of planktonic foraminifera of sediment core SH1972_16. 3 records from Channa aurantipectoralis, a new species of snakehead from Mizoram, north-eastern India (Teleostei: Channidae). 104100 records from Arizona State University Hasbrouck Insect Collection. 2 records from From an old sound recording to a new species in the genus Horatosphaga (Orthoptera: Tettigonioidea: Phaneropterinae: Acrometopini). 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 8 records from A new species of the genus Chrysacris Zheng, 1983 from China (Orthoptera: Acridoidea, Acrididae). 430 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 3587 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 25 records from Taxonomic revision of the genus Hirotophora Brown et al. (Diptera: Phoridae) with the description of a new species from Chile. 1 records from A new species and a new record of genus Hexacentrus Serville, 1831 (Orthoptera: Tettigoniidae: Hexacentrinae) from India. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 4 records from Two new species of Tardigrada (Eutardigrada: Ramazzottiidae, Macrobiotidae) from the supralittoral zone of the Atlantic Iberian Peninsula rocky shores. 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 7 records from Two new remarkable genera and two new species of Gyponini (Hemiptera: Cicadellidae: Iassinae) from Brazil. 3383 records from Lista florística de la Costa Grande del estado de Guerrero. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 7 records from Description of two new and two known species of the Genus Tylencholaimellus Cobb in M. V. Cobb, 1915 (Nematoda: Dorylaimida: Tylencholaimoidea). 351 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 2 records from Amtsrain Apolda-Zottelstedt. 12704 records from R-Criptogamos - Herbário do Museu Nacional - Criptogamos. 1 records from A new Indian record and morphological variation for Eulimnadia khoratensis Rogers et al., 2016 (Crustacea: Branchiopoda: Spinicaudata). 9 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0001A. 66116 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 36 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 17 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 3 records from A new species of Coriella, Coriella chernyshevi n. sp. (Entoprocta, Barentsiidae), with comments on the genera Coriella and Pedicellinopsis. 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 62149 records from Field Museum of Natural History (Geology) Fossil Invertebrates Collection. 94 records from Revision of the Agrilus purpurifrons species-group (Coleoptera, Buprestidae, Agrilinae). 2986 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 190 records from Apteronotus caudimaculosus n. sp. (Gymnotiformes: Apteronotidae), a sexually dimorphic black ghost knifefish from the Pantanal, Western Brazil, with a note on the monophyly of the A. albifrons species complex.. 3 records from Nomenclature and synonymic remarks on two species of Eupterotidae (Lepidoptera) described by Johan Christian Fabricius, and notes on related species. 5 records from Eulepida mbala, a new species from Zambia (Coleoptera: Scarabaeidae: Melolonthinae). 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 2 records from Dorfrand Mauderode. 6 records from Neoplecostomus canastra, a new catfish (Teleostei: Siluriformes) species from upper Rio Paraná basin. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 2485 records from Museum TwentseWelle (NL) - Fossil Sponges Collection. 215 records from Marine Plants (NHMC-SA). 68 records from New species and new records of predaceous midges in the genera, Schizonyxhelea Clastrier and Stilobezzia Kieffer from Mexico (Diptera: Ceratopogonidae). 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 7068 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 1682 records from Pollen profile from sediment core AV14_K2-3. 17367 records from K-State Museum of Entomological and Prairie Arthropod Research. 3 records from Neotype designation for Rhinogobius carpenteri Seale 1910, and its placement in Tukugobius Herre 1927 (Teleostei: Gobiidae). 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 2274 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 922 records from Diversidad y distribución geográfica de las especies de culícidos de importancia médica en la región centro-occidental de México. 29876 records from European Moth Nights. 7 records from New Species of Blindsnakes (Squamata: Gerrhopilidae) from the offshore islands of Papua New Guinea. 2 records from Review of amphipods of the genus Cryptodius Moore, 1992 (Amphipoda: Ochlesidae) from the coastal waters of Sakhalin Island (Far East of Russia). 2 records from A new addition to the subfamily Anabropsinae (Orthoptera: Anostostomatidae) from China. 255 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12523-1. 1127 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 3 records from A new species of stone loach (Teleostei: Nemacheilidae: Schistura) from Arunachal Pradesh, India. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 24795 records from Université d'Aix-Marseille. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 4 records from Four new species and new records of Atopsyche Banks (Trichoptera: Hydrobiosidae) from Pantepui biogeographical region (Venezuela). 6 records from MfN - Micropaleontology. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 12 records from BUND - Dassower See (Lübeck/Dassow). 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 259458 records from Vascular Plant Specimen database of Kanagawa Prefectural Museum of Natural History. 2036 records from Nannofossil abundance of Hole 29-277. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 36 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 3 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 18 records from Redescription of two species of wobbegongs (Chondrichthyes: Orectolobidae) with elevation of Orectolobus halei Whitley 1940 to species level.. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 32 records from Molecular study supports the position of the New Zealand endemic genus Lamellomorpha in the family Vulcanellidae (Porifera, Demospongiae, Tetractinellida), with the description of three new species. 5 records from Pseudanthias emma new species, with notes on a collection of anthiadine serranid fishes from off Myanmar (eastern Indian Ocean). 8784 records from Bryophytes specimens of Akita Prefectural Museum. 77414 records from MfN - Fossil vertebrates IV. 684 records from Estudio de la diversidad genética y su distribución de los maíces criollos y sus parientes silvestres en Michoacán. 3231 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage. 88 records from Foraminifera abundance of sediment core C1966.435. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 46019 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3439 records from MEXU/Flora de Oaxaca. 73 records from Blue Tier. 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 16 records from bmhscoralcollection. 1153 records from Nannofossil abundance of Hole 17-167. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 2 records from A new species of Pelecium Kirby (Coleoptera: Carabidae: Peleciini) from the Atlantic Forest biome, Brazil. 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 5 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 1 records from Arthropoden aus südostalpinen Höhlen.. 1 records from A new species of the genus Mongolotettix Rehn, 1928 from Hubei, China (Acrididae, Acridoidea, Orthoptera). 3 records from Range table from planktonic foraminifers in ODP Hole 139-856G. 289 records from bmhs_butterfly_collection. 8 records from Diversidad de bacterias fotótrofas en comunidades microbianas bentónicas de Bahía Concepción, BCS, México. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 21 records from From marine caves to the deep sea, a new look at Caminella (Demospongiae, Geodiidae) in the Atlanto-Mediterranean region. 22 records from BIRDRACE Birding Bentheim. 295 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 1057 records from (Appendix 2-5) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 31-296 in the western Pacific Ocean. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 16 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 13945 records from MfN - Fossil plants (Paleophytic). 1139 records from SWECO. 2 records from Taxonomic review of Stictophaula (Orthoptera: Phaneropterinae) with the description of one new species from Brunei Darussalam. 1694 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 60639 records from EAC - Herbário Prisco Bezerra. 74 records from Nannofossil abundance of Hole 37-332B. 14 records from Estudio genético de las poblaciones de Rhizophora mangle en México. 1354 records from Flora (vascular) y fauna (aves) de los Parques Nacionales del estado de Baja California: Constitución de 1857 y Sierra San Pedro Mártir. 75 records from Type material housed in the Carcinological Collection of the Museo de La Plata, Argentina. 13 records from Cnidaria ZMK. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 5 records from A cryptic new species of hummingbird of the Campylopterus largipennis complex (Aves: Trochilidae). 1 records from The extinct river shark Glyphis pagoda from the Miocene of Myanmar and a review of the fossil record of the genus Glyphis (Carcharhiniformes: Carcharhinidae). 30105 records from Collection Crustacea - ZMB. 9 records from Macrocydia divergens, a new genus and species of Grapholitini (Lepidoptera: Tortricidae: Olethreutinae) from Central America. 726 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 92 records from Ricinulei Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1200 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 4 records from Taxonomic study of the genus Meganola (Lepidoptera, Nolidae, Nolinae), with three new species and a new record from China. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 36 records from Nannofossil abundance of Hole 25-249. 87 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 12649 records from Herbario CTES Plantas Vasculares. 1448 records from Actualización de la base de datos computarizada de la colección ictiológica de la Universidad Autónoma de Baja California. 5 records from Settlement of the classification of Svistella Gorochov and Paratrigonidium Brunner von Wattenwyl using morphology and molecular techniques, with the description of a new species from Yunnan, China (Orthoptera: Trigonidiidae: Trigonidiinae). 9 records from Cephalaspidomorphs Specimens of Akita Prefectural Museum. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 110 records from Insectos del páramo de Sumapaz, Cundinamarca - Proyecto Colombia Bio. 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 6 records from Distribution of two species of Nephropsis Wood-Mason, 1872 (Crustacea, Decapoda, Nephropidae) from northeastern Brazil. 1399 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 154 records from Dermaptera in the icipe collection. 3 records from Tyrannosaurus and other Cretaceous carnivorous dinosaurs. 2344 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 30 records from On some new or rare spider species from Lesbos, Greece (Araneae: Agelenidae, Amaurobiidae, Corinnidae, Gnaphosidae, Liocranidae). 73 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 3 records from The discovery, naming and typification of Limonium gmelini (Plumbaginaceae). 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 8937 records from Röntgenarchiv Wilhelm Stürmer - SMF. 467 records from Noctuidae brasileiros de importancia economica depositados na coleção MNHUK. 115 records from Pollen record of profile 2TZ2. 1913 records from Ibaraki Nature Museum, Birds collection. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 1515 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 3 records from A new species of the genus Neobubastes Blackburn, 1892 from Western Australia (Coleoptera: Buprestidae: Buprestinae: Pterobothrini). 4 records from Two new species of Kamimuria (Plecoptera: Perlidae) from Shaanxi Province, China. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 7 records from Grammatonotus brianne, a new callanthiid fish from Philippine waters, with short accounts of two other Grammatonotus from the Coral Triangle. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 20 records from Heteroptera - SMNG. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 35865 records from Mollusca collection of National Museum of Nature and Science. 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 337 records from Pollen data of trap CB4. 15 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 24 records from A new genus and two new species of congrid eels (Teleostei: Anguilliformes: Congridae) from the Indo-West Pacific, with a redescription and osteology of Chiloconger dentatus.. 7455786 records from NMNH Extant Specimen Records. 1326 records from Collection Agnatha fossil SMF. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 15 records from Taxonomic revision of a darkling beetles genus Anaxius (Tenebrionidae: Pedinini: Helopinina). 51 records from The vespid fauna of Pakistan. 1 records from A new reticulated beetle (Coleoptera: Cupedidae) from Mexico with a catalogue of Cupedidae species of the world. 6859 records from Plan de vertebrados de la Patagonia. 13 records from A novel symbiotic relationship between mites and recluse spiders (Sicariidae: Loxosceles), with a description of a new Callidosoma species (Trombidiformes: Erythraeidae). 27 records from Jervois and Karinga Flora. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 15 records from Two new genera and two new species of cicadas from Central America (Hemiptera: Cicadidae: Cicadinae). 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 4 records from Danielsberg (Mölltal, Kärnten). 71 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 3 records from Two new species of Tenuipalpus sensu stricto (Acari: Tenuipalpidae) from Brazil with a discussion on the ontogeny of leg setae. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 119382 records from Mammalogy Collection - Royal Ontario Museum. 10 records from A new dwarf crayfish (Decapoda: Cambaridae) from floodplain swamps in central Alabama. 2 records from Rivulus kayapo n. sp. (Teleostei: Cyprinodontiformes: Rivulidae): a new killifish from the serra dos Caiapós, upper rio Araguaia basin, Brazil.. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 4044 records from SOUTHERN OCEAN ISOPODA. 5225 records from Las familias Polyporaceae sensu stricto y Albatrellaceae en México. 2 records from Cosmolaelaps Berlese (Mesostigmata: Laelapidae) from southern Brazil, with a new record of a heteromorphic male, description of a new species, and a key to the species reported from that country. 2 records from First Jurassic grasshopper (Insecta, Caelifera) from China. 3 records from A new genus of calcareous sponge discovered in the Caribbean Sea: Bidderia gen. nov. (Porifera, Calcarea, Calcinea). 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 7 records from Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China. 2 records from Two New Variegated Snailfishes of the Genus Careproctus (Teleostei: Scorpaeniformes: Liparidae) from the Aleutian Islands, Alaska. 6 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 2 records from A new genus and new species of subfamily Trioxinae (Hymenoptera: Aphidiidae) from the Far East of Russia. 128 records from Coleção de Nematoda do Museu Nacional - UFRJ. 11344 records from Colección de Plantas Vasculares del Herbario Forestal UDBC "Gilberto Emilio Mahecha Vega". 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 5 records from Review of the genus Microcurgus Haupt, 1950 (Hymenoptera, Pompilidae) with description of a new species from Iran. 6619 records from Anfibios y reptiles del estado de Tamaulipas, México. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 585 records from Livingstone Museum Bat Collection. 31251 records from International Fossil Shell Museum (NL) - Mollusca Collection. 9 records from First records of Composetia, Eunereis and Nectoneanthes (Annelida: Nereididae) from Taiwan, with descriptions of two new species. 1 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 38 records from A review of the deepwater cardinalfish genus Epigonus (Perciformes: Epigonidae) of the Western Indian Ocean, with description of two new species. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 1 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 38 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Helmut Dalitz. 772 records from Nannofossil abundance of Hole 73-519. 17 records from Reconsideration of the genera Merogomphus Martin, 1904, and Anisogomphus Selys, 1857, including erection of a new genus, with a new species and discussion of additional specimens from Cambodia. 7 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 11249 records from Heteroptera collections of SW Finland. 33782 records from CIRAD. 1 records from Cabamofa orientalis sp. nov. from Thailand, congeneric with C. mira Jaschhof from Costa Rica (Diptera: Bibionomorpha: Sciaroidea incertae sedis). 427 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Juergen Homeier. 6 records from Moribaetis brachiostrinus (Ephemeroptera: Baetidae), a new species of mayfly from Costa Rica. 4 records from Two new species of Comesomatidae (Nematoda) from the East China Sea. 67 records from Three new species of Parapercis (Perciformes: Pinguipedidae) and first records of P. muronis (Tanaka, 1918) and P. rubromaculata Ho, Chang & Shao, 2012 from Australia. 1 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 2740 records from Fungi specimens of Saitama Museum of Natural History. 1543 records from Pollen record of sediment core Bokanjacko Blato 1. 2 records from A new species of Miobantia Giglio-Tos, 1917 with a novel morphological feature (Mantodea: Thespidae: Miobantiinae). 1129 records from Mollusca Collection of Saitama Museum of Natural History. 357 records from (Appendix D) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in ODP Site 146-893. 3 records from Hyphessobrycon petricolus, a new species of tetra (Characiformes: Characidae) from the rio Madeira basin, Mato Grosso, Brazil. 97 records from POPA- Fisheries Observer Program of the Azores: Sea turtle sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 12 records from A new species of Conopsia Strand, 1913 (Lepidoptera: Sesiidae: Tinthiinae) from West Africa. 1 records from Oribates fusifer. 24 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 4 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 23 records from Kiwisaldula (Hemiptera: Heteroptera: Saldidae) from the South Island of New Zealand: new species and identification key. 602 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 12 records from Lance lacewings of the world (Neuroptera: Archeosmylidae, Osmylidae, Saucrosmylidae): review of living and fossil genera. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 75 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 46680 records from Bosque Mesófilo de Montaña de México. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 174 records from Taxonomic revision of Stagmatoptera Burmeister, 1838 (Mantodea: Mantidae, Stagmatopterinae). 4 records from A needle in a haystack: the new genus Bernadottea (Diptera: Cecidomyiidae, Winnertziinae) with four new species in the Old World. 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 120410 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 45 records from Redescription of the Indo-West Pacific cardinalfishes (Perciformes: Apogonidae) Rhabdamia spilota Allen & Kuiter 1994 and R. gracilis (Bleeker 1856). 5410 records from Collection ornithologique A. Maës. 31 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 2 records from New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey. 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 20 records from Review of the leafhopper tribe Macrostelini Kirkaldy (Cicadellidae: Deltocephalinae) in Pakistan with description of a new species. 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 89 records from Mammal specimens of Komatsu City Museum. 15 records from Two new species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Kurile Islands, Sea of Okhotsk, with a review of distinctive characters of the known species of the genus. 3 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 12 records from Two new species of bent toed geckos, Cyrtodactylus Gray, 1827 (Squamata: Gekkonidae) from Northeast India with comments on name-bearing types from the region. 1 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 1 records from Bolzplatz. 8 records from Whip spiders (Amblypygi, Arachnida) of the Western Palaearctic—a review. 5995 records from Insect (HUNM-IN). 24 records from Sternaspis chilensis n. sp., a new species from austral Chilean channels and fjords (Annelida, Sternaspidae). 1 records from Damaeus auritus. 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 318 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 306-U1313. 2 records from Basothorhynchus, a new Oosomini genus from the highland plateau of Lesotho (Coleoptera: Curculionidae: Entiminae). 3698 records from NIWA Invertebrate Type Collection. 5 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 7066 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 258 records from Malawi-Histeridae-Biodiversity-Data. 39 records from Revision of the Hoplodrina implacata group (Lepidoptera: Noctuidae: Noctuinae: Caradrinini) of Taiwan, with descriptions of four new species. 942 records from Caracterización biológica de la ventana Beltrán, corregimiento Paquiló, Municipio de Beltrán, Cundinamarca. 251 records from Fig. 7. Pollen record of profile SAO4 (Analyst: G.N. Shilova). 4439 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 25374 records from Collections of Phytoplankton at BGBM. 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 4 records from Two new species of the genus Loboschiza Diakonoff, 1968 (Lepidoptera: Tortricidae: Olethreutinae) from Thailand. 1078 records from Pollen profile from Seminary School Basin. 24 records from New species of Andiorrhinus Cognetti, 1908 (Oligochaeta: Rhinodrilidae) from Venezuela and Brazil. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 609 records from (Appendix A2) Distribution of benthic foraminifera in ODP Site 184-1146. 14 records from New enchytraeid species from Mount Hallasan (Jeju Island, Korea) (Enchytraeidae, Oligochaeta). 2 records from Two new species of the genus Deontolaimus de Man, 1880 (Nematoda: Leptolaimidae) from mangrove ecosystems of Vietnam. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 13 records from Genus Microlithosia (Lepidoptera, Erebidae, Arctiinae) in Laos, with the description of a new species. 5 records from A new species of Paratus Simon, 1898 (Araneae: Liocranidae, Paratinae) from India. 73 records from Nannofossil abundance of Hole 94-609C. 9 records from Dolichochorus Strobl 1904: a valid genus of Mesochorinae (Hymenoptera: Ichneumonidae: Mesochorinae). 1 records from Oribates calcaratus. 115 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 474606 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 10 records from A new genus of Tetracampidae (Hymenoptera) from South Africa. 1000 records from Axel W. Erikssons African Bird Collection at Vänersborg Museum. 31 records from A new Subleuconycta (Lepidoptera: Noctuidae: Acronictinae) species from Taiwan. 5335 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1882 records from Carabidae of the European North-East of Russia. 6812 records from Invertebrate collection of University of Oulu Zoological Museum. 4019 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 129663 records from University of New Mexico Herbarium. 1 records from Wassermann. 221 records from (Table 6) Ostracod assemblages of sediment core 9409. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 10 records from Beitrag zur Kenntnis der Oribatiden Mitteleuropas (Neue Liacarus-Arten). 1760 records from Herbarium of the Prioksko-Terrasnyi Biosphere Reserve. 30 records from Visual Plants (144.41.33.158) - Private collection of Manfred Kueppers. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 19951 records from Collection Aves (bird skeletons) SMF. 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 51 records from The Plecoptera of Panama. III. The genus Anacroneuria (Plecoptera: Perlidae) in Panama’s national parks: 2017 survey results. 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 2413 records from Literature based species occurrence data of birds of North-East India. 1426 records from Korean Insect Database. 3689 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 4 records from Description of three new species of Encyrtidae Walker (Hymenoptera: Chalcidoidea) from India. 1460 records from Spermatophytes collection of Okinawa Prefectural Museum & Art Museum. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 1 records from Bryozoa (Cyclostomata and Ctenostomata) from polymetallic nodules in the Russian exploration area, Clarion - Clipperton Fracture Zone, eastern Pacific Ocean-taxon novelty and implications of mining. 9 records from Three new species of Aponuphis (Annelida: Onuphidae) from eastern Australia. 70229 records from The Fish Collection. 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 127 records from Collection Ephemeroptera - SMF. 55 records from Additions and corrections to the systematics of mayfly species assigned to the genus Callibaetis Eaton 1881 (Ephemeroptera: Baetidae) from South America. 12 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 102476 records from Denver Museum of Nature & Science - Entomology. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from Entyposis cordipenis new species from Ethiopia (Coleoptera: Scarabaeidae: Melolonthinae: Schizonychini). 35 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 6 records from Hedotettix angulatus sp. nov. (Orthoptera: Tetrigoidea: Tetrigidae, Tetriginae) a new pygmy grasshopper species from India. 27 records from The land crab Johngarthia planata (Stimpson, 1860) (Crustacea, Brachyura, Gecarcinidae) colonizes human-dominated ecosystems in the continental mainland coast of Mexico. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 871 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 38841 records from Herbier de Strasbourg. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 1351 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 3 records from Naturschutzstation Schmidsfelden. 10212 records from Spider (NSMK-SP). 25491 records from OUPR - Herbário "Professor José Badini". 15 records from Nannofossil abundance of Hole 58-442B. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 4 records from VFD-H: Heidenrod: Pferdeweide Mürth. 29477 records from Manitoba Museum of Man and Nature. 10650 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 6 records from Two new terrestrial species of Hydraena Kugelann from the island of Bioko, Gulf of Guinea (Coleoptera: Hydraenidae). 18 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 182 records from Revision of the ant genus Mayriella.. 167656 records from KUBI Mammalogy Collection. 1195 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 24 records from New species of Thelepodidae (Terebelliformia, Polychaeta) from Taiwan. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 1 records from Nottekanal, Klasse 7 - 10. 311 records from Nannofossil abundance of Hole 37-333. 5923 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 10270 records from Museo Nacional de Ciencias Naturales, Madrid: Invertebrados Poliquetos. 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 201 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 2007 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from Description of Coeliccia bhriulieci sp. nov. (Odonata: Zygoptera: Platycnemididae) from central Vietnam. 6327 records from Planktonic foraminifera in ODP Hole 160-963A. 4221 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 492 records from (Table S6) Pliocene/Pleistocene benthic foraminiferal abundances from sediment core KR9912PC4. 26 records from Pachyprotasis kojimai sp. nov. — the “ Pachyprotasis nigronotata ” of Japanese authors (Hymenoptera: Tenthredinidae). 3 records from Two new species of Sphaeronemoura (Plecoptera: Nemouridae) from Oriental China. 3565 records from Sammlung Clemens Borneo Herbarium Hamburgense HBG. 1 records from A new species of Trimma (Pisces; Gobiidae) from the South-West Islands of Palau, western Pacific Ocean. 897332 records from MICROBIS database. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 604 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 1 records from A new species of the thorid genus Paralebbeus Bruce & Chace, 1986 (Crustacea: Decapoda: Caridea) from the deep sea of the Northwestern Pacific Ocean. 5710 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 36 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 293 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 15 records from The new Southeast Asian genus Cambonilla gen. nov. (Zodariidae, Araneae): ‘ bis repetita placent’. 43770 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 26753 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 3 records from A new, remarkable erigonine spider genus from eastern Asia (Araneae, Linyphiidae). 143 records from A review of the spider genus Porrhomma (Araneae, Linyphiidae). 134 records from Pollen profile II/B at Krumbach, Germany. 36375 records from Rutgers University, Chrysler Herbarium - Mycology Collection. 36162 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 9488 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 3 records from Three new species of the subgenus Ashima (Diptera: Drosophildae: Phortica) from southwestern China, with DNA barcoding information. 239 records from Indice de integridad biótica para comunidades de peces de la región alta del Río Pánuco. 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 36 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 3 records from Nationalpark Harz Schul-AG Braunlage. 1057 records from Palynological analysis of sediment core GeoB9508-5. 228 records from Colección de Quelonios Museo de La Salle Bogotá (MLS). 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 29 records from Cryptic species in the nuisance midge Polypedilum nubifer (Skuse) (Diptera: Chironomidae) and the status of Tripedilum Kieffer. 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 35325 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 35 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 199 records from Nannofossil abundance of Hole 14-142. 134 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/011-3. 569 records from Insectos del orden Trichoptera de la Sierra Tarahumara, Chihuahua, México. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 3388 records from Caracterización y evaluación de la pesquería de escribano en la región norte de Quintana Roo. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 5 records from Two new subfamilies, three new species and a new subspecies of dendrochirotid sea cucumbers (Echinodermata: Holothuroidea). 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 4490 records from Ibaraki Nature Museum, Mollusk collection. 85 records from New findings of the butterfly Phengaris teleius at the border between Hungary and Serbia (Lepidoptera: Lycaenidae). 1 records from Oribates globulus. 52 records from Review of the subgenus Tachycines (Gymnaeta) Adelung, 1902 (Orthoptera, Rhaphidophoridae, Aemodogryllinae, Aemodogryllini). 40 records from Insect - Earthworm (KIDR-IN). 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 59632 records from NCSM Herpetology Collection. 228 records from Bishop's University Insect Collection (BUIC). 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 22939 records from HURB - Herbário do Recôncavo da Bahia. 47 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 5 records from Taxonomic revision of Brasiloniscus (Oniscidea, Pudeoniscidae) with description of a new species. 265 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/090-4. 133506 records from BioFokus. 34140 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 6 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 2 records from A new species of Platypleura Amyot & Audinet-Serville, 1843 (Hemiptera: Cicadidae: Cicadinae) from the Eastern Ghats of Andhra Pradesh, India. 2 records from Orthotrichum dentatum T. Kiebacher & Lüth sp. nov. (Orthotrichaceae). 49 records from A new species of the catfish genus Cordylancistrus (Siluriformes, Loricariidae) from the Sierra Nevada de Santa Marta, Colombia. 71494 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1824 records from CNAN/Scorpiones. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 8649 records from Fossil (WSHN-FO). 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 118 records from Generic key and catalogue of Mymaridae (Hymenoptera) of Mexico. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 3571 records from Cnidarios, poliquetos, crustáceos (decápodos) y quetognatos pelágicos del Golfo de California. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 13 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 8 records from A new species of Orthosiphon (Lamiaceae) from Angola. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba (BID-AF2015-0066-REG). 2 records from A new species of Cephaloecetes (Bubocorophiina) from the Iranian coasts of the Gulf of Oman and the Hormuz Strait (Crustacea: Amphipoda: Siphonoecetini). 281 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 2443 records from Cnidaria MZS. 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 5 records from Description of a new species of Capederces (Coleoptera: Cerambycidae: Cerambycinae) from South Africa. 26 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 26 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 7351 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 13 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 40472 records from MEXU/Colección de Briofitas. 14 records from Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 907 records from Pollen profile Märchenwald B, Harz, Germany. 6 records from Mammalia (JNHM-MM). 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 458141 records from Finnish Floristic Database (Finnish Museum of Natural History Collections). 6 records from A new species of the genus Calambus C. G. Thomson, 1859 (Coleoptera: Elateridae: Dendrometrinae) from China, with notes on the other species of the genus of the East Palaearctic region. 10 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 13940 records from The Vascular Plants Collection of the University of Goettingen. 4 records from Two new species of Sochinsogonia (Hemiptera: Cicadellidae: Cicadellinae) from Philippines. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 11 records from A new species of Lycaena Fabricius, 1807 (Lepidoptera, Lycaenidae) from Mongolia with a review of genitalia characters of the related taxa. 18 records from The genus Microptila Ris (Trichoptera, Hydroptilidae) in Japan. 59 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 141 records from The Xiphydria palaeanarctica group from Japan (Hymenoptera, Xiphydriidae). 54 records from The bee Ruizanthedella mutabilis Spinola (Hymenoptera: Halictidae): a very common but poorly known species studied using integrative taxonomy. 2 records from Mainufer. 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 12 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/4 (ANDEEP II). 28 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB02 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 15 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 1 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 363 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 3 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 2 records from The discovery of Euryrhynchidae (Crustacea: Decapoda) in India, with the description of a new genus and species. 8 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 3974 records from DBL_Life. 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 859 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 4 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 6 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 3 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura: Diogenidae) from southern India. 2171 records from Thrips (Thysanoptera) in Norway. 3 records from A new species of Homo from the Late Pleistocene of the Philippines. 2 records from Deux nouvelles espèces d’ Aloe L. (Xanthorrhoeaceae, Asphodelaceae), section Lomatophyllum Rowley, de Madagascar. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 89 records from Bird specimens of Ryukyu University Museum (Fujukan). 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 2 records from A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 3 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 731 records from An updated record of Gaden Robinson's collection of Macro-moths of Fiji and Rotuma. 7 records from Sangpradubina, an astonishing new mayfly genus from Thailand (Ephemeroptera: Leptophlebiidae: Atalophlebiinae). 3 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 1764 records from Arachnida of Costa Rica (INBio). 205 records from Occurrence of some antimalarial plants from Cameroon. 3148 records from Ross A. Layberry, Collection. 3 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 24 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 26 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 8 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 247 records from Pollen analysis of sediment profile BLA00 from Blankensee. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 287 records from Nannofossil abundance of Hole 66-488. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 1915 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 1001 records from Colección Hidrobiológica del Chocó. 15 records from Two new species of the genus Sinotilla Lelej, 1995 (Hymenoptera: Mutillidae), with notes on taxonomic characters. 1 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 9304 records from Echinoderm collection of National Museum of Nature and Science. 645 records from Range table from benthic foraminifers in ODP Hole 172-1056B. 1 records from Oribates facula. 109176 records from Herps Specimens. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 37 records from COA Entomology Collection (Arctos). 30535 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 1 records from Feriendorf des Kreises Gedern (Ober-Seemen). 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 3 records from Morp
Keywords: GBIF; biodiversity; species occurrences